Burkina Faso : Questions generales. (IMF Staff Country Reports; Country Report ;, 2014)
This paper studies economic and financial spillovers from the euro area to Poland in a two-country semi-structural model. The model incorporates various channels of macrofinancial linkages and cross-border spillovers. We parameterize the model through an extensive calibration process, and provide a wide range of model properties and evaluation exercises. Simulation results suggest a prominent role of foreign demand shocks (euro area and global) in driving Poland's output, inflation and interest rate dynamics, particularly in recent years. Our model also has the capability for medium-term conditional forecasting and policy analysis.